Analisis Pelayanan Notaris pada Proses Pembuatan Akta Jual Beli di Kantor Notaris dan Pejabat Pembuat Akta Tanah Pramudita Kartikasari, S.H, M.Kn - Bella Dwi Lestari; Widyawati Widyawati; Sri Roekminiati (WISSEN : Jurnal Ilmu Sosial dan Humaniora, 2025)
This study aims to analyze the quality of notarial services in the drafting of sale and purchase deeds at the Office of Notary–PPAT Pramudita Kartikasari, S.H., M.Kn., with a focus on factors influencing client satisfaction. The research background is grounded in the essential role of notaries in ensuring legal certainty in land transactions, which requires services that are prompt, transparent, and professional. The research employed a descriptive qualitative approach through in-depth interviews, observation, and documentation, analyzed using Miles and Huberman’s interactive model. The findings indicate that service quality can be explained through the five SERVQUAL dimensions. In terms of tangibles, physical facilities were considered adequate, although the waiting area and technological equipment remained limited. The reliability dimension showed that deeds produced were legally valid and accurate, yet completion time was not always consistent. Responsiveness was generally satisfactory, though online responses were less prompt. Assurance emerged as the main strength, as the notary was able to provide legal certainty, clear explanations, and professional conduct, while empathy was reflected through attentiveness, flexibility, and personalized care for clients. Assurance and empathy were found to be dominant in enhancing satisfaction, whereas tangibles, reliability, and responsiveness require improvement. The study implies the need for facility improvements, better time management, and standardized communication, while maintaining legal certainty and empathy as the core values of notarial service.